Can Machine Translation be a Reasonable Alternative for Multilingual Question Answering Systems over Knowledge Graphs? - Perevalov, Aleksandr; Both, Andreas; Diefenbach, Dennis; Ngonga Ngomo, Axel-Cyrille (WWW ’22: The ACM Web Conference 2022, Virtual Event, Lyon, France, April 25 - 29, 2022)

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (HT ’22: 33rd ACM Conference on Hypertext and Social Media, Barcelona, Spain, 28 June 2022- 1 July 2022)

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Accessibility properties of abnormal geodesics in optimal control illustrated by two case studies - Bonnard, Bernard; Rouot, Jérémy; Wembe Moafo, Boris Edgar (Mathematical Control and Related Fields)
Keywords: Applied Mathematics; Control and Optimization; General Medicine

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

Methodenentwicklung zur numerischen Lebensdauerprognose von hyperelastischen Klebverbindungen infolge zyklischer Beanspruchung mittels bruchmechanischer Ansätze - Tews, Karina; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson; Duffe, Tobias; Kullmer, Gunter (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Automated UX Evaluation for User-Centered Design of VR Interfaces - Karakaya, Kadiray; Yigitbas, Enes; Engels, Gregor (Proceedings of the 9th International Working Conference on Human-Centered Software Engineering (HCSE'22))

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung unter Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Golebiowska, Sandra; Rieker, Florian; Ebbert, Christoph; Grundmeier, Guido

Towards Situation-specific Software Support for Cross-organizational Design Thinking Processes - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 5th International Workshop on Software-intensive Business (IWSiB'22))
Due to the increasing influences of a VUCA world, design thinking workshops have been established as a standard technique to build solutions according to uncertain customer needs. Concerning the ongoing pandemic and rising development of solutions across organizations, more and more workshops were conducted online with software support. However, existing software tools insufficiently address the different workshop situations in terms of the process (i.e., fixed tasks to conduct), the place (e.g., static online whiteboards), and people (i.e., synchronous working of all stakeholders). Therefore, we propose a design science study to develop a situation-specific software support that can be configured with flexible development processes, different places, and task-related people. Based on practical experience in existing research projects, we derive the initial design requirements and map them to a set of design principles. Out of that, we design a concept with its implementation as a software tool and point out open challenges.
Keywords: design thinking; situation-specific; cross-organizational; software support

Comparative Evaluation of AR-based, VR-based, and Traditional Basic Life Support Training - Yigitbas, Enes; Krois, Sebastian; Renzelmann, Timo; Engels, Gregor (Proceedings of the 10th International Conference on Serious Games and Applications for Health (SeGAH'22))

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (New Trends in Lithium Niobate: From Bulk to Nanocrystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Methodenentwicklung zur Auslegung geklebter Verbindungen aus hochfestem Stahl unter Berücksichtigung betriebsrelevanter Beanspruchungen im Landmaschinen- und Anlagenbau - Göddecke, Johannes; Meschut, Gerson; Göhrs, Tim; Große Gehling, Manfred

UCAI 2022 - 3rd International Workshop on User-Centered Artificial Intelligence - Buschek, Daniel; Hauptmann, Hanna; Heuer, Hendrik; Loepp, Benedikt; Riener, Andreas; Yigitbas, Enes (Proceedings of the Mensch Und Computer 2022 (MuC ’22))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Experimental Demonstration of a 2.2kW Active-Clamp Converter for High-Current Wide-Voltage-Transfer Ratio Applications - Rehlaender, Philipp; Korthauer, Bastian; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Phase-Shift Modulation for Flying-Capacitor DC-DC Converters - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

An approach for an innovative 3d steel strip straightening machine for curvature and saber compensation - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Homberg, Werner; Trächtler, Ansgar
Due to increasing globalization and rising quality requirements, the steel and metal processing industry is facing growing cost and innovation pressure. Not least because of their high lightweight potential, high-strength steel materials are meeting the growing material requirements of steel and metal processing in areas such as aerospace and medical technology. In particular, the tight tolerance limits of applicable shape and dimensional accuracies pose a challenge in the processing of high-strength steel strip materials. Improving the processability of high-strength steel materials through the use of straighteners with set-up assistance systems significantly increases the potential for competing with other materials such as aluminum or magnesium alloys.

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Multi-Objective Physics-Guided Recurrent Neural Networks for Identifying Non-Autonomous Dynamical Systems - Schön, Oliver; Götte, Ricarda-Samantha; Timmermann, Julia (14th IFAC Workshop on Adaptive and Learning Control Systems (ALCOS 2022))
While trade-offs between modeling effort and model accuracy remain a major concern with system identification, resorting to data-driven methods often leads to a complete disregard for physical plausibility. To address this issue, we propose a physics-guided hybrid approach for modeling non-autonomous systems under control. Starting from a traditional physics-based model, this is extended by a recurrent neural network and trained using a sophisticated multi-objective strategy yielding physically plausible models. While purely data-driven methods fail to produce satisfying results, experiments conducted on real data reveal substantial accuracy improvements by our approach compared to a physics-based model.
Keywords: neural networks; physics-guided; data-driven; multi-objective optimization; system identification; machine learning; dynamical systems

DigiBody - Digitale Prozesskette zur Abbildung und Optimierung der Fügetechnik im Rohbau - Jamei, Said; Döller, Norbert; Lossau, Sebastian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Sommer, Daniel; Facciotto, Silvio; Droste, Alexander; Haufe, Andre; Helbig, Martin; et al. (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)